Prevalence, Cytopathology, Histology and Hematology of Canine Transmissible Venereal Tumour in and Around Meerut District - Chaudhary, Sachin; Jaiswal, Vikas; Bhatele, Aarti; Tyagi, Surbhi Kuldeep; kumar, Prabhakar; Varma, Rachna (The Indian Journal of Animal Reproduction, 2026)
Canine Transmissible Venereal Tumor (CTVT) is a frequently diagnosed neoplasm affecting the external genitalia of  dogs, characterized by its transmission through the allogeneic transfer of living cancer cells, which typically occurs  during mating. Despite the fact that the disease has been documented in a large number of historical and modern  sources, no inclusive investigation of distribution of CTVT has been carried out, particularly in Meerut region of Uttar  Pradesh. Impression smear, FNAC and tissue biopsy samples have been collected from dogs having tumors in order to  investigate the occurrence, cytohistological and hematological characteristics of CTVT. Leishman staining for cytology  and hematoxylin& eosin for histopathology was performed along with hematology & serum biochemistry. The data  revealed 15% prevalence of all canine neoplasm with most of the CTVT cases occurring in nondescript breeds, female,  and age ranging from 1 to 8 years. All the biochemical parameters of liver function test were in normal range while hema tology showed deviation only in total & differential leukocyte counts.
Keywords: Canine Transmissible Venereal Tumour; Cytology; Histology; Haematology